2007
DOI: 10.1371/journal.pctr.0020007
|View full text |Cite
|
Sign up to set email alerts
|

Stimulatory Effect of Morning Bright Light on Reproductive Hormones and Ovulation: Results of a Controlled Crossover Trial

Abstract: Objectives:Studies have shown a shortening of the menstrual cycle following light exposure in women with abnormally long menstrual cycles or with winter depression, suggesting that artificial light can influence reproductive hormones and ovulation. The study was designed to investigate this possibility.Design:Placebo-controlled, crossover, counterbalanced order.Setting:Medical centres and participants' homes in Novosibirsk (55°N), Russia.Participants:Twenty-two women, aged 19–37 years, with baseline menstrual … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 31 publications
1
22
0
Order By: Relevance
“…In the same study, but with use of a different protocol, both morning bright light and (to a lesser extent) evening bright light increased LH secretion in the follicular and luteal stages of the menstrual cycle [61]. Another investigation that exposed women in the follicular stage of the menstrual cycle to a 45-min light pulse soon after awakening found increased levels of prolactin, FSH, and LH [30]. Ovarian follicle size and number of ovulatory cycles also increased [30].…”
Section: Ovulatory Cyclementioning
confidence: 90%
See 1 more Smart Citation
“…In the same study, but with use of a different protocol, both morning bright light and (to a lesser extent) evening bright light increased LH secretion in the follicular and luteal stages of the menstrual cycle [61]. Another investigation that exposed women in the follicular stage of the menstrual cycle to a 45-min light pulse soon after awakening found increased levels of prolactin, FSH, and LH [30]. Ovarian follicle size and number of ovulatory cycles also increased [30].…”
Section: Ovulatory Cyclementioning
confidence: 90%
“…Another investigation that exposed women in the follicular stage of the menstrual cycle to a 45-min light pulse soon after awakening found increased levels of prolactin, FSH, and LH [30]. Ovarian follicle size and number of ovulatory cycles also increased [30]. Unfortunately, these studies were not designed to determine whether the impact of bright light on the ovulatory cycle is mediated by circadian phase shift, melatonin suppression, or changes in sleep.…”
Section: Ovulatory Cyclementioning
confidence: 99%
“…Therefore, it is not unreasonable that increased ELI might synchronize menstrual cycling or promote fertility. As previously noted, Danilenko and Samoilova (2007) have shown that bright morning light promotes human fertility and modulates the menstrual cycle. Because the specificity and accuracy of the ELI/PP prediction is in close agreement with a concurrent change in European sunshine, random coincidence seems unlikely.…”
Section: Discussionmentioning
confidence: 57%
“…Further support may be found in a recent study by Danilenko and Samoilova (2007) who conclude that bright light in the morning (4300 lux) in the follicular phase of the menstrual cycle stimulates the secretion of hypophyseal reproductive hormones, promotes ovary follicle growth, and increases ovulation rates in women with slightly lengthened menstrual cycles.…”
Section: Discussionmentioning
confidence: 72%
“…36 This original report was supported and extended by findings that the menstrual cycle was shortened in 38 patients with winter depression after the daily exposure to light for 1 week as started between the days 1 and 14 of the menstrual cycle 99 and that exposure to sunshine 2 days or 3 days before the ovulation appears to shorten the men strual cycle. 100 Moreover, among women with lengthened menstrual cycles, the ovulation was promoted, the follicle size was increased, and the circulating levels of prolactin, LH, and FSH were increased by the daily exposure to bright light for 1 week between the days 7 and 14 of the menstrual cycle. 101 The effect of light on FSH secretion appears to be direct, mildly stimulating, and transient.…”
mentioning
confidence: 99%